The Roles of Kulonprogo Regional Government in Developing Tourism Economy: Nature-Based Tourism - Anggi Rahajeng (Magister Ilmu Administrasi Publik, 2016)
Tourism development requires the roles of both regional and central government. The roles of those governments in the economic development belong to the aspects of planning, policy, regulation, and public facilities development to support the tourism industry. Kulonprogo Regency has several nature-based tourism destinations that can actually be developed, but it has not been optimal yet. This study aims in determining the roles of the Government of Kulonprogo Regency in developing the tourism economy to be optimal in their area by concerning the environmental issues. This study uses the triangulation in both the data and the methods used. The theoretical approach used is the institutional economics based on the model of Williamson. The results of this study indicate that the roles of the all elements of government of Kulonprogo in the field of tourism economy development are the construction and the development of tourism destinations facilities, tourism marketing, tourism industry, and integrated related institutions. The determination of the prior destinations by the central government in 2017 was followed by the adoption of 5 zoning destinations/tourism strategic areas (KSPD) in Kulonprogo. Policies in the tourism sector is also followed by the policies on investment, particularly for infrastructure investment since the rapid growth of the investment climate and the development of mega projects in Kulonprogo (central-provincial government) to ignite the economic and the tourism development. Programs that are conducted by Kulonrogo Government through the Department of Tourism, Youth, and Sports in tourism are expected to affect the behavior/mindset of the tourism actors to concern and be more aware of tourism issues in anticipating the livelihood changes of most people in Kulonprogo (non-tourism changes into the tourism). The government should monitor and control the tourism destination development by concerning the issues of capacity, supporting capacity, and the environmental sustainability, especially around the nature-based tourism resorts.